Distinct Lung Adenocarcinoma-Associated Microbiota Are Associated with Inflammatory Immune Landscapes and Tumor Cell Proliferation via LCIIAR–ISG15 Regulatory Networks - Liu S; Zhang Z (Cancer Management and Research, 2025)
Shipu Liu,1 Zijian Zhang2 1Department of Occupational Medicine and Clinical Toxicology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of China; 2Department of Urology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100020, People’s Republic of ChinaCorrespondence: Zijian Zhang, Department of Urology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, People’s Republic of China, Email zzhang742@uwalumni.comIntroduction: Emerging research emphasizes the critical role of local microbiota in shaping the tumor microenvironment (TME) and influencing cancer progression. Lung adenocarcinoma (LUAD) is distinguished by unique bacterial communities that appear to regulate immune responses, gene expression, and patient outcomes.Methods: We compiled microbiome profiles from several cancer types—including LUAD, lung squamous cell carcinoma (LUSC), breast carcinoma (BRCA), and thyroid carcinoma (THCA)—using public databases. Non-negative matrix factorization (NMF) was employed to categorize LUAD cases based on TME features, while DESeq2 was used to pinpoint bacterial taxa with differing abundance. Multi-omics networks were developed to integrate microbial, transcriptomic, and clinical data. For in vitro verification, we conducted siRNA-mediated knockdown of the long non-coding RNA LCIIAR and ISG15 in Lewis lung carcinoma cells, followed by proliferation assays.Results: In contrast to LUSC, BRCA, and THCA, LUAD exhibited distinct microbial populations, with notable enrichment of Cylindrospermopsis, Cyanothece, and Sulfolobus. NMF clustering identified two LUAD subtypes with differing prognoses. One longer survival cluster, marked by reduced bacterial presence and stronger antitumor immunity—reflected in stronger immune response, increased effector T cells activity, and greater immune cell infiltration. A competing endogenous RNA (ceRNA) network analysis established a link between LCIIAR and ISG15, both overexpressed in LUAD and associated with worse survival outcomes. Knockdown LCIIAR or ISG15 through siRNA significantly inhibited lung cancer cell proliferation, pointing to their roles in tumor growth and ceRNA-mediated regulation.Conclusion: LUAD features a distinctive microbiota that engages with inflammatory and ceRNA regulatory pathways. These observations underscore the value of targeting microbiome-influenced mechanisms, such as the LCIIAR–ISG15 axis, as a promising approach to enhance treatment outcomes in lung adenocarcinoma.Keywords: lung adenocarcinoma, microbiota, tumor microenvironment, ceRNA network